A cat in the tree - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (Oxford university press UK, 2012)
In this story, a cat gets stuck in a tree. The children$1 (BKipper, Biff, Chip, and their friends$1 (Btry to help. They come up with different ideas, but nothing seems to work. In the end, a firefighter arrives and rescues the cat using a big ladder. Everyone is happy, and the cat is safe again!s
The Level 3 Biff, Chip and Kipper Stories, written by Roderick Hunt and illustrated by Alex Brychta, provide a rich story context to help develop language comprehension and decoding skills. Stories, More Stories A and More Stories B build on the reading skills from Level 2 and are slightly longer. First Sentences include a range of high frequency vocabulary with repetitive text to continue to build fluency. Books contain inside cover notes to support children in their reading.
H3
This story helps build early reading skills with familiar vocabulary, and it also introduces themes of teamwork and helping others. Let me know if you$1 (Bd like a lesson plan or activities to go with it!s
Keywords: Supplementary reading material